Unraveling Drug Penetration of Echinocandin Antifungals at the Site of Infection in an Intra-Abdominal Abscess Model. (4th October 2017) - Zhao, Yanan; Prideaux, Brendan; Nagasaki, Yoji; Lee, Min Hee; Chen, Pei-Yu; Blanc, Landry; Ho, Hsinpin; Clancy, Cornelius J; Nguyen, Minh-Hong; Dartois, Veronique; Perlin, David
Abstract: Background: Intra-abdominal candidiasis (IAC) is a prominent invasive fungal infection associated with high mortality. Prompt antifungal therapy and source control are crucial for successful treatment. Echinocandin antifungal drugs are first-line agents. Yet, their clinical effectiveness is highly variable with known potential for breakthrough resistance, and little is known about drug exposure at the site of infection. Using matrix-assisted desorption/ionization (MALDI) mass spectrometry imaging as well as standard analytical techniques, we investigated the spatial and quantitative distribution in tissue lesions for two echinocandin drugs, micafungin and CD101, in a clinically relevant IAC mouse model. Methods: Female 6–8 week old CD1 mice weighing 18–22 g were infected intraperitoneally (IP) with 1 × 10 7 CFU of C. albicans SC5314 mixed with sterile stool matrix. Single IP doses of CD101 at 5 or 20 mg/kg (equivalent to humanized therapeutic dose) or micafungin at 5 mg/kg (therapeutic dose) were administered to mice at day 3 post-inoculation. Mice were sacrificed at just before antifungal treatment ( n= 1), and at 1, 3, 6, 24, and 48 hours post-dose ( n = 3 per group per time point). Liver and kidney lesions were collected for MALDI imaging. Laser capture microdissection (LCM) followed by liquid chromatography coupled tandem mass spectrometry (LC/MS-MS) was applied to 6 and 24 hours samples for drug exposure measurement. In a separate experiment, mice were treated with 2 or 3 doses of micafungin (5 mg/kg), or a single dose of CD101 (20 mg/kg). Drug accumulation was analyzed at 48 and 72hours post the first dose. Results: Drug accumulation within lesions was observed with both drugs at their humanized therapeutic dose. However, micafungin, even at steady-state, failed to approach the mutant prevention concentration (MPC) (16 µg/mL) of the infecting strain. CD101 demonstrated extensive penetration into the lesions after a single dose administration and persisted in lesions at above MPC level of 29.7 µg/mL at 72 hours postdose. Conclusion: These findings indicate that current echinocandin drugs may be limited by penetration at the site of infection, which have implications for clinical outcomes and emergence of resistance in patients with IAC. Disclosures: C. J. Clancy, Merck: Received research funding, Research support; Astellas: Received research funding, Research support; Cidara: Received research funding, Research support; Astellas: Scientific Advisor, Advisory board; Merck: Scientific Advisor, Advisory board; Cidara: Scientific Advisor, Advisory board; Medicines Company: Scientific Advisor, Advisory board; D. Perlin, Cidara: Research Contractor and Scientific Advisor, Research grant; Amplyx: Research Contractor and Scientific Advisor, Research grant; Matinas: Scientific Advisor, Research support; Scynexis: Research Contractor and Scientific Advisor, Research grant; Merck: Research Contractor, Research grant; Astellas: Research Contractor,  Research grant